Artificial General Intelligence (AGI) and Its Implications For Contract Law - Wahyudi Umar; Sudirman Sudirman; Rasmuddin Rasmuddin (Indonesian Journal of Artificial Intelligence and Data Mining, 2023)
The development of artificial intelligence technology has presented AGI as an exciting future potential. In contract law, AGI can change the landscape of agreements and contract execution. The existence of AGI will raise various legal challenges and questions, such as whether AGI can be a legal party to a contract, whether AGI can execute contracts effectively, and how legal responsibility AGI is in contract execution. This study aims to analyze and identify the legal implications that may arise with the existence of AGI in the context of contract law. In this regard, the research will try to understand how AGI can influence existing principles of contract law. This study uses normative research methods by collecting and analyzing relevant legal sources, including legal literature, regulations, and court rulings related to contract law. This research also involves a comparative study of existing contract law with possible future situations with the existence of AGI. The results of this study show that the presence of AGI has the potential to change important aspects of contract law. Some of the implications identified include questions about AGI's legal status as a legal subject, AGI's legal liability in the performance of contracts, aspects of the validity and interpretation of contracts involving AGI, and legal protection for parties entering transactions with AGI. This research provides a crucial initial understanding in dealing with legal challenges that may arise due to the existence of AGI in the context of contract law